1991
DOI: 10.1073/pnas.88.10.4328
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of transcription factor NF-kappa B binding activity by oxidation-reduction in vitro.

Abstract: NF-icB is a widely used regulator of inducible and tissue-specific gene control. In the cytosol, when complexed to an inhibitory molecule, IKB, NF-#cB is in an inactive form and cannot bind DNA. Activation of cells with appropriate stimuli results in the dissociation of NF-mcB from IjcB and its translocation to the nucleus as an active binding protein. We now demonstrate that NF-ucB binding in vitro can be inhibited by agents that modify free sulfhydryls. Binding is eliminated after treatment with N-ethylmalei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
280
0

Year Published

1995
1995
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 603 publications
(292 citation statements)
references
References 38 publications
12
280
0
Order By: Relevance
“…The promoter region of cyclin D1 gene contains binding sites for redox-sensitive transcription factors including cyclic adenosine monophosphate response element-binding protein, nuclear factor-kB (NF-kB), activator protein 1 and Sp1. Several reports show redox modifications of critical cysteines in these transcription factors regulate their DNA-binding activities (Abate et al, 1990;Toledano and Leonard, 1991;Manome et al, 1993;Ohba et al, 1994;Janssen et al, 1995;Lo and Cruz, 1995). Hence, redox-state-dependent modulation of the activity of these transcription factors could significantly influence cyclin D1 transcription.…”
Section: Intracellular Redox State and Cell Cycle Proteinsmentioning
confidence: 99%
“…The promoter region of cyclin D1 gene contains binding sites for redox-sensitive transcription factors including cyclic adenosine monophosphate response element-binding protein, nuclear factor-kB (NF-kB), activator protein 1 and Sp1. Several reports show redox modifications of critical cysteines in these transcription factors regulate their DNA-binding activities (Abate et al, 1990;Toledano and Leonard, 1991;Manome et al, 1993;Ohba et al, 1994;Janssen et al, 1995;Lo and Cruz, 1995). Hence, redox-state-dependent modulation of the activity of these transcription factors could significantly influence cyclin D1 transcription.…”
Section: Intracellular Redox State and Cell Cycle Proteinsmentioning
confidence: 99%
“…Unlike the bacterial peroxide sensor OxyR that can be activated by oxidation in vitro, oxidation of purified NF-KB-IKB does not activate but even causes a loss of DNA-binding activity [38]. A conserved cysteine residue in the DNA-binding domain of NF-KB subunits seems to be responsible for this oxidative inhibition [39].…”
Section: Roi-induced Intracellular Signal Transductionmentioning
confidence: 99%
“…Both Trx1 and 2 play essential biological roles in mammals. Some of the physiologically important roles of Trx include: 1) acting as a hydrogen donor for enzymes involved in reductive reactions [38]; 2) maintaining a reduced environment in cells [9]; 3) controlling protein (especially transcription factors) function via the redox state [1012] and the expression of target genes; 4) protecting cells and tissues from oxidative stress [13]; and 5) having anti-apoptotic effects through the inhibition of the ASK [14] and mitochondrial pathways [15]. The essential biological roles of Trx were further supported by two studies which demonstrated that mice null for either Trx1 or Trx2 were embryonically lethal [16,17].…”
Section: Introductionmentioning
confidence: 99%